The adequacy of foreign reserves and their role in the stability of the exchange rate of the Iraqi dinar (Journal of Accounting and Financial Studies ( JAFS ), 2022)
Many countries are very important in their interest not only in diversifying foreign reserves, but in determining and planning their volume in accordance with the goals set, namely facing potential external shocks, as the research aims to determine the extent of the strength of foreign reserves in the possession of the Central Bank in relation to every influential variable in the Iraqi economy. , in order to determine the minimum level of reserves that requires reconsideration of the exchange rate, as the research adopted the inductive analytical method in analyzing real (Quantitative data) for the research variables in the years of study, as the research adopted a set of analytical indicators approved by the International Monetary Fund, Among these indicators are (the ratio of coverage of foreign reserves to imports, the ratio of coverage of foreign reserves to the gross domestic product, the ratio of coverage of foreign reserves to the broad money supply M2, the ratio of coverage of foreign reserves to foreign debt with interest, the ratio of coverage of foreign reserves to the exported currency). In addition to a suggestion of an analytical indicator that fits with the Iraqi monetary reality, which is (the ratio of coverage of foreign reserves to the sales of the currency sale window), through which the results and conclusions were reached, the most important of which was that the foreign reserves are characterized by very high adequacy indicators, and this gives a feeling of reassurance in the long run. The average towards internal and global events, but in the long run and with the continued total dependence on the rentier economy (single source of the dollar), the indicators of the adequacy of reserves enter the scope of uncertainty, especially with the most important indicator of sufficiency, which is the ratio of foreign reserves to imports due to the lack of the real production base.